Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.
Chapter 14

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Améliorer la santé et le bien-être des Madelinots anglophones. Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Anglophone Magdalen Islanders, 2017)
fs-ref-orig: Burke, H., Craig, L. et Richardson, M. (2017). Améliorer la santé et le bien-être des Madelinots anglophones. Une évaluation des besoins : mieux comprendre la situation actuelle des aînés. Council for Anglophone Magdalen Islanders. fs-code-orig: Burke-2017

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)
fs-ref-orig: Commissariat aux langues officielles. (2017). L’offre active une culture de respect, une culture d’excellence : guide complet. fs-code-orig: Commissariat aux langues officielles-2017.

Accessibility and active offer: Health care and social services in linguistic minority communities - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (University of Ottawa Press, 2017)
This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. Action based, it will help shape the leaders of tomorrow. It is imperative that we train leaders who are able to intervene efficiently with service users and to support a better organization of the workplace. It is especially important to look at the many issues related to postsecondary training and human resources, such as recruiting and keeping these leading professionals. Accessibility and Active Offer thus combines theory and empirical data to help future professionals understand the workplace issues of accessibility and active offer of minority-language services. This English-language adaptation of Accessibilité et offre active features an additional chapter by Richard Bourhis on issues specific to Anglophone communities in Québec.

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011). Statistics Canada. fs-code-orig: Lepage-2017b

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011). Statistique Canada. fs-code-orig: Lepage-2017a

Health care professionals and official-language minorities in Canada, 2001 and 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistics Canada, 2017)

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistique Canada, 2017)

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre active, acteurs et système de santé et de services sociaux : un cadre d’analyse - Vézina, Sylvain; Savard, Sébastien (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Ce chapitre présente un cadre théorique inspiré de l’analyse stratégique aussi nommée sociologie des organisations. Par cette approche, le chercheur tente de découvrir les objectifs et stratégies des acteurs en présence pour mieux saisir la dynamique du système d’action tout en prenant en compte les contraintes issues de la structure formelle. On y traite des concepts de système d’action, de pouvoir, de règle du jeu, de changement, de stratégie, d’acteur, d’enjeu, d’organisation et d’environnement, lesquels rendent compte de la complexité des défis entourant la pratique de l’offre active en santé et services sociaux. Une des contributions majeures de cette approche est qu’elle fournit un cadre d’analyse permettant de mieux saisir la relation entre l’acteur et le système, deux composantes essentielles tant à la compréhension de notre objet qu’à l’identification de stratégies d’action par les acteurs du milieu. Mots-clés : offre active, services sociaux et de santé, système d’action, pouvoir, zone d’incertitude, analyse stratégique, sociologie des organisations, changement, stratégie, acteur, enjeu, organisation, environnement.
Chapitre 1